The Influence of Contextual Teaching Learning Audio Visual Media Learning Models on Student Learning Outcomes on Digestive System Material in Class XI Private High School Pab 8 Saentis Medan - Mutia Febri Sadiq; Khairuddin; Khairunna (Marga: Journal Of Innovation and Creatifity, 2024)
The background to this research is that the learning implemented by teachers has not provided optimal learning results on the digestive system material. This research aims to test the influence of the Contextual Teaching And Learning (CTL) learning model with audio visual media on the learning outcomes of digestive system material in class XI students at PAB8 Saentis Medan Private High School. The specific aim of this research is to test the differences in learning outcomes on digestive system material between the experimental class which applies the CTL model and the control class and to test whether there is an influence on student learning outcomes in the experimental class using the CTL model. The research method used is the experimental method. The design in this research is a quasi experimental design with a non-equivalent control group design. The population in this study was class XI IPA 3 as the experimental class and XI IPA 4 as the control class. The dependent variable in this research is the learning outcomes in the digestive system material and the independent variable is the CTL learning model. The technique for collecting data on learning outcomes uses multiple choice tests. The research results show that: (1) there are differences in learning outcomes in the experimental class and the control class as shown by the results of the independent samples T-test significance (2-tailed) = 0.036 < 0.05. (2) there is an influence on the learning outcomes of experimental class students who use the CTL model with an average posttest score of 81, which previously was only 69.29. The suggestion is that the CTL learning model with audio visual media should be used as an alternative learning process on digestive system material in schools because it has a positive effect and is applied by teachers to create active learning.